Antibiotic Resistance Patterns of Group B Streptococcal Clinical Isolates - Jose A. Simoes; Alla A. Aroutcheva; Ira Heimler; Sebastian Faro (Hindawi Limited, 2004)
Objectives: To determine the in vitro resistance of group B streptococcus (GBS) to 12 antibiotics. To determine if there has been any decrease in sensitivity to the penicillins or other antibiotics currently used for GBS chemoprophylaxis in pregnant women. Find suitable alternative antibiotics to penicillin. Find an antibiotic that will have minimal selective pressure for resistance among the endogenous resident vaginal microflora.